INVESTMENTS NON GRATAE: INFORMAL RESTRICTIONS ON CAPITAL FLOWS IN THE ЕURASIAN ECONOMIC UNION (EURASEC) MEMBER COUNTRIES - M. M. Lobanov (Финансы: теория и практика)
The article focuses on the problems of investment cooperation between the EurAsEC countries caused by informal restrictions on the movement of capital. An analysis of investment activities of foreign companies in the markets of these countries allows to reveal at least seven types of informal constraints (introduced under the influence of various factors) which impact on the interaction between recipients and donors of capital. In this context, the author evaluates the prospects of creating conditions for the free movement of capital within the EurAsEC and proposes measures to remove barriers to foreign investment. It is noted that irrational bureaucratic management is another barrier to foreign investment and it is often mentioned by entrepreneurs as one of the main investment risks. The negative impact of bureaucracy on the company's work can take on various forms: from incompetence in making decisions to direct intervention in business processes. Also, a very common practice in business is changing “the rules of the game”. For example, before signing investment agreements, foreign companies count to obtain benefits and preferences which can be eliminated later, in the process of project implementation. In this case, low predictability of decisions and actions of the authorities acts as an informal barrier to investment.